Chemical composition and biological activities of extracts and essential oil of Boswellia dalzielii leaves - Midéko Justin Kohoude; Fernand Gbaguidi; Pierre Agbani; Marc-Abel Ayedoun; Sylvie Cazaux; Jalloul Bouajila (Taylor & Francis Group, 2017)
Context: Boswellia dalzielii Hutch. (Burseraceae) is an aromatic plant. The leaves are used for beverage flavouring. Objective: This study investigates the chemical composition and biological activities of various extracts. Materials and methods: The essential oil was prepared via hydrodistillation. Identification and quantification were realized via GC-MS and GC-FID. Consecutive extractions (cyclohexane, dichloromethane, ethyl acetate and methanol) were carried out and various chemical groups (phenolics, flavonoids, tannins, antocyanins and sugar) were quantified. The volatile compounds of organic extracts were identified before and after derivatization. Antioxidant, antihyperuricemia, anti-Alzheimer, anti-inflammatory and anticancer activities were evaluated. Results: In the essential oil, 50 compounds were identified, including 3-carene (27.72%) and α-pinene (15.18%). 2,5-Dihydroxy acetophenone and β-d-xylopyranose were identified in the methanol extract. Higher phenolic (315.97 g GAE/kg dry mass) and flavonoid (37.19 g QE/kg dry mass) contents were observed in the methanol extract. The methanol extract has presented remarkable IC50 = 6.10 mg/L for antiDPPH, 35.10 mg/L for antixanthine oxidase and 28.01 mg/L for anti-5-lipoxygenase. For acetylcholinesterase inhibition, the best IC50 (76.20 and 67.10 mg/L) were observed, respectively, with an ethyl acetate extract and the essential oil. At 50 mg/L, the dichloromethane extract inhibited OVCAR-3 cell lines by 65.10%, while cyclohexane extract inhibited IGROV-1 cell lines by 92.60%. Discussion and conclusion: Biological activities were fully correlated with the chemical groups of the extracts. The ethyl acetate and methanol extracts could be considered as potential alternatives for use in dietary supplements for the prevention or treatment of diseases because of these extracts natural antioxidant, antihyperuricemic and anti-inflammatory activities.